Primary Furlow Palatoplasty for Delayed Repair of Veau Type I Cleft Palate in an Adolescent: Surgical Challenges and Bio-functional Outcomes - Al Hafiz; Hazazi Nur Adli Aroli; Emilia Nissa Khairani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Cleft palate is a pervasive congenital craniofacial anomaly characterized by the failure of palatal shelf fusion, resulting in a persistent communication between the oral and nasal cavities. While developed healthcare systems mandate repair between 9 and 12 months, delayed presentation in adolescence remains a distinct clinical entity in developing regions. These cases are surgically complex due to maxillary skeletal maturity, tissue fibrosis, and wider cleft gaps compared to infant cases. The primary surgical objective is to seal the defect and restore the velopharyngeal sphincter to prevent hypernasality. This study evaluates the efficacy and physiological advantages of the Furlow double opposing Z-plasty technique in a high-risk delayed primary repair scenario. Case presentation: We report the management of a 14-year-old male presenting with an uncorrected non-syndromic incomplete cleft palate. Preoperative assessment revealed severe hypernasality and audible nasal air emission. Clinical examination confirmed a Veau Type I defect confined to the soft palate with a bifid uvula. Primary palatoplasty was executed using the Furlow technique. The procedure successfully recruited lateral tissue for palatal lengthening and achieved transverse muscle reorientation without the need for lateral relaxing incisions. Conclusion: The intervention resulted in complete anatomical closure with no evidence of wound dehiscence, hemorrhage, or oronasal fistula formation. The Furlow technique proved to be a feasible and safe modality for Veau Type I defects in adolescents, effectively addressing the vertical pharyngeal gap and restoring the sphincter mechanism's anatomy.